Pengaruh Kepemilikan Saham Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode 2013-2017 - Putri Yuri Astika; Patar Marbun; Eka Dewi Setia Tarigan (Universitas Medan Area, 2020)
This study aims to determine whether Share Ownership (X1) and Corporate Social Responsibility (X2) both partially and simultaneously have a significant effect on the Value of Manufacturing Companies Listed on the IDX. The data analysis method used is the classic assumption test, multiple linear regression analysis and hypothesis testing. The data used in this study is secondary data, by collecting financial statements of Manufacturing Companies in the form of balance sheets and income statements for 2013 up to 2017 which are listed on the Indonesia Stock Exchange. The sample used in this study was 10 samples. Based on the results of the study, the researchers suggested that manufacturing companies listed on the Stock Exchange can increase share ownership thereby increasing the value of the company so that the profits obtained by the company are high and also affect dividend payments because the market considers that high dividend payments reflect good corporate performance and provide good prospects in the future.